Optimization of Flowchart Material in Programming Using Problem Based Learning Model Class X SMKN 1 Cerme - Cahyani, Marisania Pramesti; Rosmelati, Malinda Putri; Aziz, Maretha Rendy Ahmadan Abdul; Romadhoni, M. Aldo Fatkur; Fani, Listania Dunu; Sulthoni, Maulana; Harimurti, Rina; Hikmah, Milhatul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to analyze the optimization of flowchart material in programming through the application of the PBL model in class X of SMKN 1 Cerme. The method used is Classroom Action Research with two cycles, involving 36 students of class X Visual Communication Design (DKV) 1. Data collection was carried out through cognitive tests, learning interest questionnaires, and learning motivation questionnaires. The results of the study showed a significant increase in the cognitive learning outcome aspect, with the average pretest score increasing from 67.5 to 74.9 and the posttest score from 80.9 to 89.9. The results of the paired t-test showed that the implementation of PBL had a positive impact on students' academic achievement. The increase was also seen in students' learning interest, indicated by an increase in the percentage of learning completion from 81% to 97%. In addition, students' learning motivation increased, with the highest score in cycle I of 4.53 in the aspect of facility availability, and increasing to 4.69 in cycle II in the aspect of belief in the relevance of flowchart learning to the world of technology. The conclusion of this study shows that the PBL model is effective in improving student learning outcomes, interests, and motivation. The implication is that teachers are advised to implement problem-based learning that is contextual and relevant to the needs of students and the world of work.